Structures for regional development to support rural development - Florin Marian Buhociu; Dragos Horia Buhociu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
The purpose of this paper is to identify and evaluate directions, methods, and specific instruments of territorial development having a major positive impact both economically and socially, on rural development. This is based on information obtained in the country of Galati, in close correlation with those similar in neighboring counties of Braila and Tulcea, all three counties being structures located in the Development Region 2 South- East. At Galati county level analysis and studies were carried out on the opportunity and economic efficiency of the establishment of a Metropolitan Area enabling economic and social development of Galati Municipality as well as of an adjacent rural areas, to include cities fromneighboring counties Braila and Tulcea...
Keywords: 330; regional development; rural development; Metropolitan Area; pole of urban development; zone of economic influence